2023
DOI: 10.1002/cncr.34718
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation increases objective response rate and prolongs progression‐free time in patients with advanced melanoma undergoing anti–PD‐1 therapy

Abstract: Background Vitamin D3 is a prohormone with pleiotropic effects, including modulating the functions of the immune system and may affect the effectiveness of anti–PD‐1 treatment in patients with cancer. According to the literature, the potential mechanism of vitamin D's influence on the effectiveness of therapy is most likely related to the amount and activity of tumor‐infiltrating lymphocytes. There are data showing the effect of vitamin D on cells regulating the activity of CD8 lymphocytes. Methods A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Similarly, VDR expression in melanoma correlates with immune score and increased patient survival, possibly because VDR signals help counteract immunosuppressive Wnt signaling ( 69 ). Notably, a recent study has reported that greater VitD levels at baseline or after dietary correction correlate with higher responsiveness to immune checkpoint blockade therapy in a cohort of advanced melanoma patients ( 70 ). Thus, in humans, as in mice, VitD activity appears to potentiate immune responses to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, VDR expression in melanoma correlates with immune score and increased patient survival, possibly because VDR signals help counteract immunosuppressive Wnt signaling ( 69 ). Notably, a recent study has reported that greater VitD levels at baseline or after dietary correction correlate with higher responsiveness to immune checkpoint blockade therapy in a cohort of advanced melanoma patients ( 70 ). Thus, in humans, as in mice, VitD activity appears to potentiate immune responses to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D, further, upregulates MAP kinases, inhibits the NF-kB signaling pathway, regulates cytokine levels, and modulates the interaction between tumor cells and immune cells. It also plays a role in regulating the prostaglandin pathway [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important to maintain a stable vitamin D level within the normal level during anti-PD-1 immunotherapy, which improves patients’ prognosis [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not report on whether these micronutrient deficiencies were remedied, such supplementation should perhaps be considered in the face of such deficiencies. As another example, Galus et al 14 studied 200 patients with melanoma, all of whom were receiving anti–programmed death-L1 therapy. Serum vitamin D levels were assessed.…”
Section: Should I Take a Regular-dose Supplement?mentioning
confidence: 99%